Long‐Term Time‐Varying Risk of Readmission After Acute Myocardial Infarction. Issue 21 (6th November 2018) - Khot, Umesh N.; Johnson, Michael J.; Wiggins, Newton B.; Lowry, Ashley M.; Rajeswaran, Jeevanantham; Kapadia, Samir; Menon, Venu; Ellis, Stephen G.; Goepfarth, Pamela; Blackstone, Eugene H.
Abstract : Background: Readmission after myocardial infarction (MI) is a publicly reported quality metric with hospital reimbursement linked to readmission rates. We describe the timing and pattern of readmission by cause within the first year after MI in consecutive patients, regardless of revascularization strategy, payer status, or age. Methods and Results: We identified patients discharged after an MI from April 2008 to June 2012. Readmission within 12 months was the primary end point. Readmissions were classified into 4 groups: MI related, other cardiovascular, noncardiovascular, and planned. A total of 3069 patients were discharged after an MI (average age, 65±13 years; and 1941 [63%] men). A total of 655 patients (21.3%) were readmitted at least once (897 total readmissions). A total of 147 patients (4.8%) were readmitted ≥2 times, accounting for 389 readmissions (43%). The instantaneous risk of all‐cause readmission was highest (15 readmissions/100 patients per month; 95% confidence interval, 12–19 readmissions/100 patients per month) immediately after discharge, decreased by almost half (8.1 readmissions/100 patients per month; 95% confidence interval, 7.2–9.0 readmissions/100 patients per month) within 15 days, and was substantially lower and relatively constant (1.4 readmissions/100 patients per month; 95% confidence interval, 1.2–1.6 readmissions/100 patients per month) out to 1 year. Cardiovascular causes of readmission were more common early after discharge. Conclusions: Most patients with MI are never readmitted, whereas a small minority (≈5%) account for nearly half of 1‐year readmissions. The readmission pattern after MI is characterized by an early peak (first 15 days) of cardiovascular readmissions, followed by a middle period (months 1–4) of noncardiovascular readmissions, and ending with a low‐risk period (>4 months) during which the risk appears independent of cause. Abstract : See Editorial by Levy and Allen